Effects of a 10-week dry-land strength and conditioning program in physical capacities and start of previously federated and regular swimming practitioners - Silva, Carlos; Jesus, João; Vilarigues, Iuri; Aranha, Ivo; Candeias, Iuri; Santos, Fernando; Figueiredo, Teresa; Espada, Mário (Cuadernos de Psicología del Deporte, 2022)
The aim of this study was to evaluate the effects of a 10-week strength and conditioning (S&C) program in physical capacities and start in previously federated and regular swimming practitioners. 16 swimmers (9 male, 17.00±2.16 years of age, 179.14±5.76 cm of height and 69.79±3.11 kg of weight; 7 female, 15.86±2.34 years of age, 163.86±4.98 cm of height and 60.19±3.60 kg of weigh) were equality, but randomly separated in two groups (control group and experimental group, CG and EG, respectively). In the pre-test, swimmers performed three starts in two different models, grab start and track start, the best start was registered. Kinematic parameters of the swimming start and time at 15 m were determined. Flexibility, countermovement jump and 3 kg medicine ball throw were also assessed. In post-test, 10-weeks after a regular 2-sessions week specific dry-land S&C program of 60 min was performed by the EG, all tests were repeated. Flexibility, strength and muscular power gains were significant in EG, contrarily to CG. Swimming start flight phase variables improved more in EG compared to CG, with specificities observed in grab and track start but not a linear consequence with performance in 15-m mark in both groups. A 10-week dry-land S&C program can provide benefits in physical capacities in regular swimming practitioners, fact that may improve the initial phase of the swimming start, prior to the underwater moment, which should deserve attention by the coaches in daily training aiming performance enhancement at 15 m.